Clinical research and prevention: fundamental elements of sustainable health care systems based on patients’ needs (Italian Journal of Public Health, 2011)
Problems in health care systems are present on a planetary scale due to a discrepancy between scarceresources and vast needs. These are mainly generated by the aging of the population. Everywhere in the world,state health care agencies simply reduce the quantity and eventually the quality of available services. Thisapproach is unacceptable, at least in Europe, where health care is a legal right, granted from birth to death.This paper departs from the poor support available nowadays for clinical research and the trivial investmentson prevention, and hypothesizes a new approach based on clinical research and prevention which, in the longterm, would generate a just, efficient, sustainable health care system stemming from patients’ needs. This isdiscussed from various viewpoints. It emerges that there is a need to switch the focus of health systems awayfrom cures towards prevention and as well as a need for better translational research. It is of note that inFrance such a program based on clinical research and prevention was launched in 2008
Keywords: prevention; clinical research; sustainable health care; economists; philosophers; physicians